HUBUNGAN INDEKS MASSA TUBUH TERHADAP KELINCAHAN ATLET PENCAK SILAT AL ASROR SEMARANG - Gilang Gemilang Muti (Unnes Journal of Sport Sciences, 2023)
This research aims to explore the correlation between body mass index and agility among Al Asror Pencak Silat athletes participating in Semarang 2022. The main objective is to determine the impact of body mass index on the athletes' agility. The research utilized correlational methodology, employing a one-shot case study design. It focused on body mass index and athlete agility among 30 male athletes from Al Asror Semarang 2022 Pencak Silat. The sampling technique employed was simple random sampling. According to the study findings, there is a correlation between body mass index and agility among Al Asror Semarang 2022 Pencak Silat athletes, with a p-value of 0.051 and α of 0.05. The study concludes that the lack of correlation between the two variables is due to additional factors like muscle mass and fat intensity in BMI. Thus, selecting BMI alone is insufficient for assessing athlete agility. Future researchers should focus on data variables and deepen their understanding of BMI and agility.